(untitled) (Kinesiology, 2022)
This study aimed to investigate the existence of relative age effect (RAE) in male Brazilian futsal athletes according to age categories and playing position. Data from male futsal athletes from the top five teams in Brazil were collected during May and June 2021. The distribution of birth dates of 387 male futsal athletes was analyzed, based on their age categories (U15, n = 97; U17, n = 88; U20, n = 116; senior, n = 86) and playing positions (defender, n = 76; winger; n = 162; pivot, n = 69; goalkeeper, n = 80). Chi-squared tests were used to analyze the birth dates distribution based on quarter and semesters of the year according to age categories and playing positions. The overall analysis of birth quarter indicated a higher occurrence of births in the first quarter of the year (p<.001; V = 0.188). The age categories analysis indicated a uniform distribution in U15 (p=.09; V = 0.15) and unequal distributions in U17 (p<.001; V = 0.29), U20 (p<.007; V = 0.19) and senior (p<.01; V = 0.21) categories. The playing position analysis indicated a uniform distribution for the pivots (p=.11; V = 0.17) and unequal distribution for goalkeepers (p<.04; V = 0.19), wingers (p<.002; V = 0.19) and defenders (p<.002; V = 0.27). We concluded that RAE was present in Brazilian elite men’s futsal, especially in the U17, U20, and senior categories, and goalkeepers, wingers, and defenders. Our results reinforce the need to consider the effects of relative age in the development of Brazilian elite futsal players. Key words: RAE, birth-date, birth effect, talent selection, elite athletes